2005
DOI: 10.1021/ma051121s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chemical Degradation of Branched Vinyl Polymers Prepared via ATRP:  Use of a Cleavable Disulfide-Based Branching Agent

Abstract: Highly branched poly(2-hydroxypropyl methacrylate) has been prepared by atom transfer radical polymerization (ATRP) in methanol at 20 °C using a disulfide-based dimethacrylate (DSDMA) branching agent. The mean degree of polymerization of the primary chains was fixed at 50; since ATRP has reasonably good living character, the molecular weight distribution of these primary chains is relatively narrow, which allows significantly better control than conventional radical polymerization. Varying the proportion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
224
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(240 citation statements)
references
References 45 publications
16
224
0
Order By: Relevance
“…To further prove that our proposed strategy leads to such a highly branched structure, a cleavable polymer was designed and prepared via in situ DE-ATRP from a degradable disulphide divinyl monomer (DSDA) 35 . Within the DSDA monomer is a disulphide bond that can be cleaved quickly under reducing conditions, thus allowing us to observe the degradation profile and hence determine if a hyperbranced structure (will be degraded into small units) or a cyclized structure (will 'untie' into a linear chain) is formed.…”
Section: Discussionmentioning
confidence: 99%
“…To further prove that our proposed strategy leads to such a highly branched structure, a cleavable polymer was designed and prepared via in situ DE-ATRP from a degradable disulphide divinyl monomer (DSDA) 35 . Within the DSDA monomer is a disulphide bond that can be cleaved quickly under reducing conditions, thus allowing us to observe the degradation profile and hence determine if a hyperbranced structure (will be degraded into small units) or a cyclized structure (will 'untie' into a linear chain) is formed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] There has been great interest in the synthesis of polymers with disulfide linkages using a variety of polymerization methods. 4,[8][9][10][11][12] We have shown with the use of a difunctional reversible addition-fragmentation transfer (RAFT) agent that a,x-telechelic poly(styrene) (PSTY) (with thiol end-groups) 13,14 was synthesized with chains of near uniform length. 15 These chains upon oxidation formed monocyclic structures with one disulfide linkage under dilute conditions or linear multiblocks with many disulfide linkages under concentrated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…37 Further studies on polymer PPB 3 have revealed the unique ability of the material to undergo self-assembly reorganization into core-shell nanoparticles upon polyanion complexation.…”
Section: Discussionmentioning
confidence: 99%
“…The disulfide functionality can be cleaved under reducing conditions using tributyl phosphine, [32][33][34] dithiotreitol (DTT), [35][36] or glutathione (GSH). 37 spectra were recorded on a 400 MHz Avance Bruker NMR spectrometer. Chemical shifts were reported in parts per million (ppm) for 1 H NMR on the δ scale based on the middle peak (δ = 2.50 ppm) of the dimethylsulfoxide (DMSO)-d6 solvent as an internal standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation